Catalogue of cacaos conserved at CRC Genebank - Bekele, Frances; Bidaisee, Gillian; Bhola, Junior; Umaharan, Pathmanathan (Bioversity International, 2024)
The International Cocoa Genebank, Trinidad (ICGT), is regarded as the largest and most diverse cacao (Theobroma cacao L.) collection in the public domain with over 2300 accessions of cacao held as a field collection in Trinidad and Tobago. The Cocoa Research Centre of the University of the West Indies (CRC-UWI; www.sta.uwi.edu/ cru) is the custodian of this international cacao collection. This along with the cacao collection at CATIE, Costa Rica (abbreviated IC3) are the only two cacao collections in the public domain supporting global cacao breeding programmes. The ICGT was established through consolidation of a number of historic collections held in local estates originating from expeditions carried out during the period 1935-1970 into countries that are part of the centre of diversity of cocoa (eg. Peru, Ecuador and Colombia). The 34 ha land, in which the cacao field collection is held, is part of the La Reunion Estate, Centeno, Trinidad and Tobago; and was generously provided to the University of the West Indies by the Government of the Republic of Trinidad and Tobago (GORTT) under a 99-year lease arrangement. The collection was initially established with support from the European Development Fund through a project carried out during the period 1981-86. The collection was incorporated under Article 15 of the International Treaty on Plant Genetic Resources for Food and Agriculture. Subsequently (post 1990), accessions were added through collections from other parts of Latin America and the Caribbean region under various projects, particularly from French Guiana and other Caribbean countries. The genebank actively supports cacao breeding programmes through supply of germplasm and germplasm services.